Crystal structure of the co-crystal of 5-aminoisophthalic acid and 1,2-bis(pyridin-4-yl)ethene - Scott C. McGuire; Steven C. Travis; Daniel W. Tuohey; Thomas J. Deering; Bob Martin; Jordan M. Cox; Jason B. Benedict (Acta Crystallographica Section E: Crystallographic Communications, 2016)
In the title 1:1 co-crystal, C12H10N2·C8H7NO4, the bipyridine moiety shows whole-molecule disorder over two sets of sites in a 0.588 (3): 0.412 (3) ratio. In the crystal, the components form hydrogen-bonded sheets linked by N—H...O and O—H...N interactions, which stack along the a axis. A comparison to a related and previously published co-crystal of 5-amino-isophthalic acid and the shorter 4,4′-bipryidine is presented.